Perception of Malaysian Women in the Labour Market – does One have to be Present to be Productive? - Subramaniam, Geetha; Maniam, Bala; Rasiah, Ratneswary; Dzulkarnain, Siti Mahara (International Journal of Engineering and Technology, 2018)
In today’s dynamic work environment, flexible working arrangements is a work policy discussed commonly by both employers and employees. However, in a developing country like Malaysia the issue is that employers still equate presenteeism with productivity. Using a self-administered questionnaire, 256 working women were surveyed to examine their perception of FWAs and productivity. The main aim of this study was to examine to what extent do the women perceive that physical presenteesim at the workplace may have an impact on their productivity at work. Findings show that age is an important demographic factor which influences the demand for FWAs. The results also show that nature of work, perceptions about FWAs and family friendly policies have significant influence on the perception that FWAs increase productivity. Providing support network and incentives in terms of tax deduction will encourage more employers to provide FWAs and this should be the policy in place. These results have some far-reaching implications on talent loss and the Malaysian labour market if workplace strategies are not implemented immediately.